How the State Education Agencies Addressed Gifted Education in the Title II Sections of Their ESSA State Plans. Issue 3 (July 2018) - Kaul, Corina R.; Davis, Brenda K.
In 2015, the U.S. Congress passed the Every Student Succeeds Act (ESSA) that included provisions to support gifted and talented learners. The U.S. Department of Education's Consolidated State Plan template only required states to directly address the inclusion of gifted education under Title II, Part A: Supporting Effective Instruction (Section 2101(d)(2)(J)). We examined the inclusion of gifted education in the Title II section of all 52 submitted ESSA plans. Of the approved plans, 16 states explicitly addressed how educators would be supported in identifying and providing gifted learners with effective instruction, and 15 states generally described educator support to meet the needs of multiple groups of students (including gifted). Three of the approved state plans did not mention support for gifted education in their Title II responses. Gifted education stakeholders must be familiar with their state's plan and understand how Title II can fund professional development for gifted education.